Functional significance of the STEVOR multigene family of plasmodium falciparum - Madnani, Kripa Gopal (2016)
Functional Significance of the STEVOR Multigene Family of Plasmodium Falciparum The STEVOR proteins represent one of the three major variant antigen families of P.falciparum. Although they have been shown to be expressed at all stages of parasite development, their functions are largely unexplored. This work focuses on their role during the blood stages of parasite development within the human host. Here, we show that STEVOR is an important ligand for parasite rosetting and that it interacts with Glycophorin C on the surface of the uninfected RBC. In addition, we show that molecule clusters on the surface of the infected RBC. We also demonstrate that the cytosolic domain of the protein interacts with the actin cytoskeleton and that this interaction is partially responsible for the increase in rigidity seen at the late asexual stage and also at stages III and IV of gametocyte development. Interestingly, we found that this interaction is not a pre-requisite for molecular clustering at the late asexual stages. Thus, in this work we show that STEVOR is a protein that is capable of mediating multiple functions on the iRBC surface.